Management of congenital quantitative fibrinogen disorders: a Delphi consensus. (19th September 2016) - Casini, A.; de Moerloose, P.; ,
Abstract : Introduction: No evidence‐based guidelines for the management of patients suffering from afibrinogenaemia and hypofibrinogenaemia are available. Aim and method: The aim of this study was to harmonize patient's care among invited haemophilia experts from Belgium, France and Switzerland. A Delphi‐like methodology was used to reach a consensus on: prophylaxis, bleeding, surgery, pregnancy and thrombosis management. Results: The main final statements are as follows: (i) a secondary fibrinogen prophylaxis should be started after a first life‐threatening bleeding in patients with afibrinogenaemia; (ii) during prophylaxis the target trough fibrinogen level should be 0.5 g L −1 ; (iii) if an adaptation of dosage is required, the frequency of infusions rather than the fibrinogen amount should be modified; (iv) afibrinogenaemic patients undergoing a surgery at high bleeding risk should receive fibrinogen concentrates regardless of the personal or family history of bleeding; (v) moderate hypofibrinogenaemic patients (i.e. ≥0.5 g L −1 ) without previous bleeding (despite haemostatic challenges) undergoing a surgery at low bleeding risk may not receive fibrinogen concentrates as prophylaxis; (vi) monitoring the trough fibrinogen levels should be performed at least once a month throughout the pregnancy and a foetal growth and placenta development close monitoring by ultrasound is recommended; (vii) fibrinogen replacement should be started concomitantly to the introduction of anticoagulation in afibrinogenaemic patients suffering from a venous thromboembolic event; and (viii) low‐molecular‐weight heparin is the anticoagulant of choice in case of venous thromboembolism. Conclusion: The results of this initiative should help clinicians in the difficult management of patients with congenital fibrinogen disorders.